Printing of drug carriers using extrusion-based printing - Chan, Kenny Hsiu Kah (2019)
In recent years, 3D printing has gained popularity in the pharmaceutical industry to manufacture customized medicine by controlling the dosages, shapes, sizes and release profiles. The idea of customized medicine might turn into a reality in the near future when tailor-made prescriptions become commercially available. This project aims to explore the possibilities of creating an interval release drug known as a multiple-release polypill. A polypill was designed to house three separate compartments, each capable of delaying drug release until the desired time interval. The polypill will be able to help patients with conditions like diabetes by allowing them to consume just one tablet a day. A pressure-assisted microsyringe system was used to extrude specially formulated hydrogels to form the polypill. Tablet segments were printed separately, dried and measured. The segments were evaluated individually for their drug release profile. The results were promising as drug release was significantly delayed before the intended timed-release and rapid after the shell was dissolved. Improvements could be made in the future to improve the delayed release as well as increasing the rate of dissolution of the drug-loaded core.